Nursing Ethics as a Foundation in Nursing Practice: A Literature Review - Dewi, Ni Made Ratih Comala; Aryana, I Gusti Ngurah; Bela, I Kadek Miki Indra; Widiastuti, Ni Kadek Nefi; Putra, I Kadek Andika Dwi; Satriani, Ni luh Adi (Babali Nursing Research, 2024)
Introduction: Complexity in the healthcare environment causes problems in nursing practice. The nursing code of ethics has been designed as an appropriate guideline for behavior and helps decision-making. Nursing ethics requires nurses to comply with ethical principles to produce quality nursing care. Therefore, this study aims to illustrate the importance of nursing ethics as a foundation for nursing practice.Methods: In the case of the current research, the articles were selected according to PRISMA guidelines. A literature review used three journal databases: ScienceDirect, PubMed, and Google Scholar. The keywords in this literature review are adjusted to the Medical Subject Heading (MeSH), which consists of "nursing ethics," "code of ethics," AND "professional nurse." Several inclusion criteria were set to obtain eligible articles published between 2014 and 2023 and written in English and Bahasa. Fifteen eligible articles were finally included in the analysis.Results: These findings highlight the critical role of understanding ethics, integrity, and moral responsibility and the importance of nursing codes of ethics in implementing nursing practice to improve the quality of nursing care and improve the quality of care Conclusion: Nursing ethics is ethos. Integrity and moral responsibility are at the heart of ethics. Nurses must have an understanding of ethics for self-development and nursing services. As a relevant source, the code of ethics refers to the system of rules. Applying the code of ethics in nursing practice improves the quality of nursing care and service to guarantee patient safety.